The Impact of Hepatitis B Vaccine Failure on Long-term Natural Course of Chronic Hepatitis B Virus Infection in Hepatitis B e Antigen–Seropositive Children - Tai, Chi-San; Wu, Jia-Feng; Chen, Huey-Ling; Ni, Yen-Hsuan; Hsu, Hong-Yuan; Chang, Mei-Hwei (The Journal of infectious diseases, 2017)
Summary Vaccine failure with chronic hepatitis B virus (HBV) infection still develops in children after universal hepatitis B immunization. Vaccine failure HBV-carrier children were associated with delayed hepatitis B e antigen seroconversion, and more HBV genotype C infection. Abstract Background Vaccine failure with chronic hepatitis B virus (HBV) infection still develops in children after universal hepatitis B immunization. This study aimed to investigate the natural course of chronic HBV infection in children with vaccine failure and compare it with that of nonvaccinated children. Methods Three hundred fifty-six hepatitis B e antigen (HBeAg)–seropositive, hepatitis B surface antigen (HBsAg) carrier children, who were followed for at least 1 year without antiviral therapy, were enrolled. These comprised 105 vaccine failure subjects who received 3 doses of HBV vaccine in infancy and 251 nonvaccinated subjects. The clinical, serologic, and virologic features were compared between the 2 groups. Results The cumulative HBeAg seroconversion rate was significantly lower in the vaccine failure group than in the nonvaccinated group (30.5% vs 77.7%, P < .0001). Genotype C HBV infection was more frequent in the vaccine failure group (33.7% vs 13.4%, P < .0001), and the maternal HBsAg-positive rate was higher (97.1% vs 66.4%, P < .0001). In a multivariate analysis, vaccine failure, genotype C infection, and maternal HBsAg positivity were significantly associated with delayed HBeAg seroconversion. Conclusions HBeAg-seropositive vaccine failure HBV-carrier children were associated with delayed HBeAg seroconversion during long-term follow-up, and more HBV genotype C infection and maternal HBsAg seropositivity.